Individual case safety reports by nursing staff: a retrospective pharmacovigilance analysis - T., Padmavathi; P., Rajavel Murugan (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The burden of adverse drug reactions is high and accounts for considerable morbidity which can be prevented if healthcare professionals have proper knowledge. Early and spontaneous reporting of ADRs is the mainstay of pharmacovigilance program. Since staff nurses are closely involved in direct patient care, they can easily identify ADRs in the early stage. This study was done to assess the extent of participation of nurses in pharmacovigilance program in our institution. Methods: Retrospective observational study was conducted by analyzing the 210 Individual Case Safety Reports (ICSR) of 2years duration. Causality assessment in the ICSR was analyzed. Severity of the reactions was categorized into mild, moderate and severe according to Modified Hartwig and Siegel scale. Descriptive statistics were used. Results: There were 177 cases reported by faculties and 33 were by the staff nurses.19 nurses reported 33 adverse effects (1:1.7) whereas 41 faculties 177 events (1:4). On analyzing the severity of reactions, 188 cases were categorized as moderate (89.5%), 20 mild (9.5%) and 2 severe (1%). In moderate category of 188 reports, 82 % reporting was by faculties and 18% by staff nurses. All the 33 reports by nurses were of moderate category (100%). In the mild and severe category, 100% reporting was by faculties. Causality analysis showed that 194 were classified as probable (92%), 14 as Possible (7%) and 2as certain (1%). In probable category 85% of reporting was by faculties and 15% by nurses, in possible group 71 % by faculties and 29% by nurses and 100% by faculties in severe category. Conclusions: Training and dedicated participation of nurses can improve reporting of ICSR.